Assessment of Sustained Systemic Inflammatory Response Syndrome and CSF Markers as Predictive Values Associated with Shunt-Dependent Hydrocephalus after Aneurysmal Subarachnoid Hemorrhage - Elghity, Ahmed; El Halaby, Walid; Raafat, Wleed; Sorour, Omar; Atallah, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
Aim of the study: This study was conducted to detect incidence and risk factors of shunt-dependent hydrocephalus, including Systemic Inflammatory Response Syndrome. Patients and methods: After obtaining ethical approval from the research ethics committee of Cairo University, this study was conducted in two phases, phase I in the form of follow up study to detect the incidence of shunt dependent hydrocephalus in patients with ruptured subarachnoid aneurysm then phase II in the form of comparative one to detect the risk factors of acquisition of shunt dependent hydrocephalus and detect the predictive role of SIRS in SDH. The study included 90 patients with ruptured subarachnoid aneurysms followed up in the department of neurosurgery of Cairo university hospital from April 2018 to April 2020. Results: The incidence of shunt-dependent hydrocephalus was 28% among the studied patients with significant association with high-grade SIRS, Fisher score, Hunt and Hess score, and leukocytosis. The CSF white blood cells and protein were significantly higher in the hydrocephalus group. Also, there was significant hypernatremia among the hydrocephalic group. Conclusion: Despite the study's analytical design, we observed a link between high fisher, SIRS, hypernatremia, and shunt-dependent hydrocephalus in aneurysmal SAH patients. Serum sodium, CSF WBCs, and protein may all be used to predict HC.